Multimedia learning stations : facilitating instruction, strengthening the research process, building collaborative partnerships - Spisak, Jen (Tech tools for learning., 2015)
"Learn how to use rotating multimedia learning stations, employing databases, websites, education apps, videos, audio podcasts, online games, books, and more to build a strong, collaborative library program that helps you strengthen student understanding of the research process"--